Văn học Việt Nam thế kỷ XX - Nguyễn, Ngọc Thiện (Văn học, 2009)
Giới thiệu các bài lý luận và phê bình của nhiều tác giả: Hà Minh Đức, Phan Cự Đệ, Lê Đình Kỵ, Đỗ Đức Hiếu, Nguyễn Văn Hạnh, Phương Lựu...